2020
DOI: 10.3390/math8040571
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Non-Trivial Fuzzy Inner Product Spaces and the Cauchy–Schwartz Inequality

Abstract: First, we show that the non-trivial fuzzy inner product space under the linearity condition does not exist, which means a fuzzy inner product space with linearity produces only a crisp real number for each pair of vectors. If the positive-definiteness is added to the condition, then the Cauchy–Schwartz inequality is also proved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In [18], it is mentioned that the author couldn't prove the converse of their proposed theorem would hold in terms of fuzzy context except the crisp case (see the subsection 3.1). In our previous study [3], we have proved that the converse in terms of fuzzy context can not hold. In fact, it was shown that a fuzzy inner product on a vector space, producing a fuzzy real number as its value for each tuple of elements in the space, is merely the embedding of a real valued inner product into the fuzzy number systems over the set of tuples consisting of elements in the space because of its linear property.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…In [18], it is mentioned that the author couldn't prove the converse of their proposed theorem would hold in terms of fuzzy context except the crisp case (see the subsection 3.1). In our previous study [3], we have proved that the converse in terms of fuzzy context can not hold. In fact, it was shown that a fuzzy inner product on a vector space, producing a fuzzy real number as its value for each tuple of elements in the space, is merely the embedding of a real valued inner product into the fuzzy number systems over the set of tuples consisting of elements in the space because of its linear property.…”
Section: Introductionmentioning
confidence: 91%
“…But, this fuzzy real inner product is a trivial one in the sense that it is the embedding of a real-valued inner product into the fuzzy real number systems over the set of tuples consisting of elements of a give vector space, which is shown in [3] or see the subsection 3.2. Thus we need to change the conditions of Definition 2.6 into weak ones.…”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations